Governance amid bigger, better markets - Donahue, John D.; Nye, Joseph S. (Brookings Institution Press, 2001)
Annotation Changing markets are challenging governance. The growing scale, reach, complexity, and popular legitimacy of market institutions and market players are re-opening old questions about the role of the public sector and redefining what it means to govern well. This volume -- the latest publication from the Visions of Governance in the 21st Century program at the Kennedy School of Government -- explores the way evolving markets alter the pursuit of cherished public goals. John D. Donahue and Joseph S. Nye, Jr. frame the inquiry with an essay on governing well in an age of ascendant markets. Other contributors (all from Harvard's Kennedy School unless otherwise indicated) address specific areas of market governance in individual chapters: Joseph P. Newhouse on the medical marketplace, Jose Gomez-Ibaqez and John R. Meyer on transportation, William Hogan on electric power, Paul E. Peterson on K12 education, L. Jean Camp on information networks, Akash Deep and Guido Schaefer (Vienna University of Economics & Business Administration) on federal deposit insurance, Frederick Schauer on "the marketplace of ideas," Anna Greenberg on the "marketization" of politics, David M. Hart on the politics of high-tech industry, Viktor Mayer-Schvnberger on information law, John D. Donahue and Richard J. Zeckhauser on the challenges posed by fast-changing markets, and Mark Moore on the spread of market ideology
"Visions of governance in the 21st century, Cambridge, Massachusetts."
Keywords: Capitalism.; Corporate governance.; Political culture.; Gouvernement d'entreprise.; POLITICAL SCIENCE -- Political Process -- Political Advocacy.; BUSINESS & ECONOMICS -- Public Finance.; Capitalism; Corporate governance; Political culture